Role of Nadi Shodhana Pranayama in Lung Function Improvement - Sharma, Aakanksha; Bhushan Sharma, Vijay; Kumar Mishra, Pramod (International Research Journal of Ayurveda & Yoga, 2025)
Pranayama, is a traditional yogic breathing method that improves respiratory functioning and balances energy. Although Pranayama has been shown to offer potential therapeutic advantages in several studies, there is little study on how it affects healthy people. The effects of Nadi Shodhana Pranayama on pulmonary functions in healthy volunteers are amplified in this case series. Objectives: Using metrics such as oxygen saturation (SpO2) level in healthy individuals, forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and FEV1/FVC to evaluate the impact of Nadi Shodhana Pranayama on pulmonary functions. Materials and Methods: A total of 20 healthy volunteers were instructed to practice Nadi Shodhana Pranayama 30 times daily over 45 days. Spirometry was used to measure pulmonary function both before and after the operation. Subjective sensations with breathing and general sensations were also recorded. Results: Following the intervention, all individuals’ pulmonary function improved. Significant increases in FVC, FEV1, and SpO2 levels suggested greater air flow, increased oxygen absorption, improved lung capacity, and a more effective respiratory system. Conclusion: Nadi Shodhana Pranayama appears to significantly improve pulmonary function in healthy volunteers, according to the findings. It has the potential to improve health and well-being if it is incorporated into a daily routine. Although the results are encouraging, it is recommended that large-scale studies and randomized controlled trials be conducted to investigate its potential long-term benefits in a variety of populations.